2004
DOI: 10.1046/j.1439-0426.2003.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periphyton on growth performance of grey mullet, Mugil cephalus (Linn.), in inland saline groundwater ponds

Abstract: The present study attempts to assess the potential of artificial substrates to enhance fish production in inland saline groundwater ponds through periphyton production. Grey mullet, Mugil cephalus, was cultured for 100 days in ponds with substrate (treatment ponds) and without substrate (control ponds). To enhance the surface area, bamboo poles were used as substrate. The periphyton population, pigment concentration and hydrobiological characteristics of pond water were monitored. The studies revealed little d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…For chlorophyll a , a known amount of water was filtered through Whatman filter paper (no. 40) and determined (see Jana et al., 2004 for details) following Boyd (1990).…”
Section: Methodsmentioning
confidence: 99%
“…For chlorophyll a , a known amount of water was filtered through Whatman filter paper (no. 40) and determined (see Jana et al., 2004 for details) following Boyd (1990).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the information is on fresh water system showing that the various substrates contribute to growth and production of the different cultured species (Wahab et al 1999; Thompson et al 2000; Tidwell et al 2000; Azim et al 2001; Keshavanath et al 2001). Reports by Jana et al . (2004, 2006) have shown that colonization of periphyton on bamboo poles increase the growth rate of brackishwater finfish Mugil cephalus (35%) and Chanos chanos (73%) cultured in saline groundwater ponds.…”
Section: Introductionmentioning
confidence: 93%
“…This species is widely cultured in both brackish and freshwater semi-intensive fishponds [23] and can utilize both supplemental feed and/or natural food [24]. Studies on food and feeding habit of stripped grey mullet worldwide indicates that the food spectrum is mainly constituted with Diatoms, green and blue green algae, Dinoflagellates, Protozoa, macro plant detritus, Copepods, Nematodes and Foraminifera according to the order of dominance [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%